Evaluación de la administración, gestión y el derecho de sucesión de las empresas familiares en el Ecuador y propuesta alternativa de un modelo administrativo familiar periodo 2013-2015. - Tinitana Aguilar, Kerly Paola (2015)
This thesis studied very thoroughly to family businesses and their importance in the economy of our country as a base for growth. If it is true, with the objective of such companies is to satisfy the needs of the family and generate a heritage that will last until the new generations is undeniable problem that occurs when happen either shares or shares. During the development of family businesses, efforts have been made to locate the problems and what are the factors leading success in the succession of family businesses are in which it is established that the main problems occur in the differences occur between old partners and new partners as successors, appear as clearly differences of opinion as to the management and administration of the company. Family firms, when being formed, are managed by entrepreneurs who have shown their full effort to develop as entrepreneurs, always showing values of humility and solidarity, because these businesses generate jobs faithfully contribute to the development of country.